The european paediatric legislation: benefits and perspectives - Rocchi Francesca; Paolucci Paolo; Ceci Adriana; Rossi Paolo (BMC, 2010)
Abstract Background The lack of availability of appropriate medicines for children is an extensive and well known problem. Paediatricians and Physicians who take care of the paediatric population are primarily exposed to cope with this negative situation very often as more than half of the children are prescribed off-label or unlicensed medicines. Discussion Medicinal products used to treat this population should be subjected to ethical research of high quality and be explicitly authorised for use in children as it happens in adults. For that reason, and following the US experience, the European Paediatric Regulation has been amended in January 2007 by the European Commission. The objective of the Paediatric Regulation is to improve the development of high quality and ethically researched medicines for children aged 0 to 17 years, to facilitate the availability of information on the use of medicines for children, without subjecting children to unnecessary trials, or delaying the authorisation of medicines for use in adults. Summary The Paediatric Regulation is dramatically changing the regulatory environment for paediatric medicines in Europe and is fuelling an increased number of clinical trials in the paediatric population. Nevertheless, there are some risks and pitfalls that need to be anticipated and controlled in order to ensure that children will ultimately benefit from this European initiative.